Aplikasi Pencarian Tempat Ibadah Gereja Dan Vihara Berbasis Mobile - Jimmy Laso M; Emmy Wahyuningtyas (Melek IT : Information Technology Journal, 2016)
Information about search Places of worship, especially church or temple is not much information about places of worship, but many people feel confused, especially new students who are generally new entrants from outside Surabaya because of the difficulty in finding a place of worship is sought.In this final project will be built an application based Mobile is powered by the Web Service as facilities for to provide location data church / monastery in Form view maps by using googlemaps as a basic digital map information that aims to simplify the search for the location of Places of Worship along route lokasti toward the destination. In order for the system that has been designed to be implemented then it takes some mobile devices, supporting software and data information of places of worship which are located around Surabaya.We make application Search Location Places of Worship Church and Worship Based Mobile is expected to help the new students who are generally new entrants from outside the city of Surabaya to look for a place of worship to be desired and supported by their route to the location of the destination in the form of display maps with google maps as a digital map